The dimensions of entrepreneurial orientation in franchise networks: Exploring the role of franchisee associations - Peter Balsarini; Claire Lambert (Administrative Sciences, 2024)
This study explores how a state-based franchisee association of a multinational quick-service restaurant franchisor introduced three world-first innovations through the activation of the five dimensions of entrepreneurial orientation (EO). The antecedents to this activation were also explored. A historical extended case study focusing on a revelatory case was undertaken. In-depth analysis using a rigorous qualitative methodology was facilitated by the triangulation of informant interviews, publicly available data, archival data, and artefacts. The three innovations explored involved the apparent activation of all five dimensions of EO by the franchisee association. The franchisee association's structure and the provenance of its franchisee members, in being either externally recruited or internally recruited, appeared to have a bearing on whether product or process innovations were pursued. Five antecedents that enhance the propensity of franchisee associations to activate the dimensions of EO were also identified, and a preliminary model was constructed. Whilst the EO of franchisors and franchisees has previously been examined, this study is the first to explore franchisee associations as a vehicle for EO. With around 75% of franchisors incorporating some form of franchisee association, better understanding how to harness their innovative potential could bestow a competitive advantage upon those franchise systems able to do so.
Keywords: 350; collaboration networks; entrepreneurial orientation; franchisee associations; franchising; innovation